An overview of the recurrent failures of duplex stainless steels. (March 2019) - de Farias Azevedo, Cesar Roberto; Boschetti Pereira, Henrique; Wolynec, Stephan; Padilha, Angelo Fernando
Abstract: The favourable combination of mechanical and corrosion properties of ferritic-austenitic duplex stainless steels (DSSs) makes this class of materials widely employed in many industries (e.g. petrochemical, nuclear, pulp and paper). Despite their wide and growing usage, the DSS components might be subjected to various types of mechanical and environmentally induced failures during their life cycle, especially when the component is exposed to temperatures in the range of 300 to 900 °C, which might promote the precipitation of stable and deleterious phases. For instance, the precipitation of sigma, alpha-prime and M23 C6 phases - the latter more often observed in high carbon DSS – might induce the premature failure of DSS components due to the mechanical embrittlement and the sensitization of the microstructure during thermal exposure (either in processing, such as welding, or in service). Additionally, the ferrite phase features a ductile-to-brittle temperature, which defines the lower service temperature of DSS components. In this sense, the main properties of DSSs will be compared with the properties of austenitic stainless steels (ASSs) and ferritic stainless steels (FSSs) to provide the reader a broader view about boundary conditions for the selection and use of DSSs. The main phase transformations and microstructures of the DSSs will be concisely presented and microstructural, fractographic and crack propagation characterization of selected in-service failures will illustrate the role of these stable and deleterious phases on the life of DSS components. Highlights: An overview of the recurrent failures of duplex stainless steels (DSSs) is presented. The main phase transformations and microstructures of wrought and cast DSSs were shown. The main properties of DSSs were compared to austenitic and ferritic stainless steels. Selected in-service cases of failures analysis of DSS components were presented. The restrictions for the selection, processing and use of DSSs were concisely shown.